Girls and Young Women in Community Sport: A South Australian Perspective - Drummond, Murray; Drummond, Claire; Elliott, Sam; Prichard, Ivanka; Pennesi, Jamie-Lee; Lewis, Lucy K.; Bailey, Christopher; Bevan, Nadia (Frontiers in Sports and Active Living, 2022)
Girls' and young women's engagement and disengagement in physical activity has been well documented in Western culture. Sport plays a pivotal role in the development of behaviours that promote physical activity, particularly through commitment to team and individual goal attainment, socialisation, and feelings of belonging and self-identity. Community sport in Australia is the dominant pathway into state, national, and elite international competition. The importance of community sport in the lives of girls and young women cannot be overstated, irrespective of individual long-term sporting goals. Indeed, the dropout rate of girls in sports, like many other western cultures is significant and is certainly disproportionate to the numbers of boys who drop out. The present study aims to examine the intrapersonal, interpersonal, and environmental influences on community sporting pathways for girls and young women. Using a mixed-methods design, we include survey data from 2,189 high-school students (aged 12–18 years) and focus group and individual interview data from a subset of 37 high-school students, parents, and teachers, across metropolitan Adelaide, South Australia. The study included an examination of sporting practises and insights of male sport participants from the same age groups to juxtapose the findings and provide a more comprehensive understanding of girls' and young women's community sporting involvement. Parents and teachers were also included within the participant cohort to provide a comprehensive perspective. The results highlight the challenges that girls face with respect to engagement and disengagement in sport and particular points throughout their adolescent years. Recommendations are provided to help mitigate potential attrition of girls in sport in the future.